A atuação do profissional de pedagogia no CAPS AD de Abaetetuba-Pará - PINHEIRO, Luciele Belém (2025)
This article seeks to show the importance of the pedagogy professional's work in a non-school environment, focusing on CAPS ad (Alcohol and Drug Psychosocial Care Center), highlighting the role of the pedagogue in a multidisciplinary team that aims to include people in psychological distress as a result of alcohol and drug use. The questions that guided the study were: What is the social importance of CAPS ad and its multi-professional teams? What is the role of the pedagogue on the premises of the CAPS ad? What is the relationship between mental health and pedagogy? The general objective of the study is to analyze how the pedagogy professional works at the CAPS ad in Abaetetuba, as well as the development of the activities carried out there with patients undergoing treatment, demonstrating the transcendence of pedagogical 4 support. The specific objectives of this work are: To discuss the social importance of CAPS ad and the work of the multi-professional teams, to analyze the professional work of the pedagogue in CAPS ad and to understand the relationship between metal health and the professional of Pedagogy. The methodology used in the research was based on a qualitative approach, which allows a more in-depth understanding of the participants' experiences, combined with bibliographical research that enables the theoretical foundation of the work, as a data collection instrument a semi-structured interview script was used. , in order to broaden the understanding of the role of the pedagogy professional at CAPS ad. As results, we understand the transcendence of pedagogical support for people undergoing treatment at CAPS ad in Abaetetuba-Pará, given that this support aims, through activities that have therapeutic purposes, to enable rehabilitation, strengthen socialization, social development and promotion quality of life of people who are in psychological distress as a result of the use of alcohol and other drugs.